2019
DOI: 10.1002/jcop.22293
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and parent–child relationship: A cross‐sectional study of adolescents

Abstract: We examined the association between social media use and parent–child relationship quality and tested whether this association is independent of total screen time. Data on 9,732 students (48.4% female) aged 11–20 years were obtained from a provincially representative school‐based survey. Heavy use of social media (daily use of more than 2 hr) was associated with greater odds of negative relationships between mother–daughter (odds ratio [OR] = 1.79; 95% confidence interval [CI]: 1.27–2.52), father–daughter (OR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
(66 reference statements)
1
20
0
2
Order By: Relevance
“…One of few studies examining SMU and family connectedness, a cross-sectional survey of Canadian adolescents [ 29 ] found that heavy SMU (3 or more hours per day) was associated with greater odds of negative reported relationships between mothers and daughters, fathers and daughters and fathers and sons, but not mothers and sons. The authors explain their results as indicative of SMU displacing time spent engaging face-to-face with parents, with negative consequences for family relationships, However, our findings indicate that adolescents may also be motivated to turn to social media as a result of existing poor family connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…One of few studies examining SMU and family connectedness, a cross-sectional survey of Canadian adolescents [ 29 ] found that heavy SMU (3 or more hours per day) was associated with greater odds of negative reported relationships between mothers and daughters, fathers and daughters and fathers and sons, but not mothers and sons. The authors explain their results as indicative of SMU displacing time spent engaging face-to-face with parents, with negative consequences for family relationships, However, our findings indicate that adolescents may also be motivated to turn to social media as a result of existing poor family connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…Among multiple factors that shape sociability, environmental influences such as familiar education, parental bonding and adult attachment play a role in regulating in-person and online sociability [37,38,39,40,41]. According to the prototypical hypothesis of attachment, the relational patterns with peers and the partner are influenced by the early relationships with parents during infancy and childhood, which appear to be stable throughout life [42,43,44,45].…”
Section: Environmental Influences On Socialization and Their Interplay With The Oxytocin Receptor Genementioning
confidence: 99%
“…Social media sites are particularly popular among adolescents and young people (Sampasa-Kanyinga et al, 2020). They provide users with a profile space, facilities for uploading content (e.g., photos), messaging, and the capability to make connections with other people.…”
Section: Introductionmentioning
confidence: 99%